Inversión extranjera y construcción de ferrocarriles en Colombia : the Panama Railroad Co. (1850-1903) (2009)
The mid-nineteenth century set the stage for one of the most successful process of foreign investment in Latin America and particularly in Colombia, at least from the perspective of foreign investors: the construction and operation of the Panama Railroad Co. However, unlike other similar experiences in which the railroads were paramount for the integration of regional and national markets and helped to construct the imaginary of the concept of a nation, this was not the Colombian case. In addition to the late and dysfunctional transport system, the Panama Railroad Co., became one of key elements that would eventually help to question the degree of Colombian sovereignty over Panama.